Characteristics of the bacterial flora in the conjunctival sac of cats from Poland. (5th December 2014) - Kiełbowicz, Z.; Płoneczka‐Janeczko, K.; Bania, J.; Bierowiec, K.; Kiełbowicz, M.
<x xml:space="preserve">Abstract</x> OBJECTIVES To assess the bacterial flora of the conjunctival sac in clinically healthy cats and cats with signs of conjunctivitis. METHODS A total of 324 conjunctival swabs were examined between 2011 and 2012 taken from 60 animals, 30 of which were clinically healthy and 30 with signs of chronic conjunctivitis. The samples were taken three times at 4‐week intervals from the clinically healthy cats. The samples from the cats with conjunctivitis were taken before and 4 weeks after cessation of successful therapy. Swabs from both the right and left eye of each cat were subjected to microbiological examination and polymerase chain reaction for the presence of DNA of Chlamydophila felis and Mycoplasma felis. RESULTS There was no qualitative difference in the eye microflora between the clinically healthy animals and those with signs of conjunctivitis. Staphylococcus epidermidis (21 · 9%) was the most common microorganism isolated and it was more commonly detected in swabs from cats with conjunctivitis (P < 0 · 0001) as was Staphylococcus aureus (P = 0 · 07). The presence of C. felis was significantly correlated with (P < 0 · 0001) signs of conjunctivitis and was detected in 25% of swabs collected from both conjunctival sacs. No DNA of M. felis was detected in any swab. None of the animals had sterile conjunctival sacs in all consecutive bacteriological tests. CLINICAL SIGNIFICANCE The conjunctival sac in cats was sterile in over 50% of the clinically healthy cats and 25% of the cats with conjunctivitis. The sterility did not persist for longer than 4 weeks. Positive bacterial cultures occur in cats with and without clinical signs of conjunctivitis.